Achados timpanométricos em um grupo de escolares - Lindau, Tâmara De Andrade [UNESP] (2013)
PURPOSE: to characterize and compare the tympanometric findings in a group of preschoolers. METHOD: 112 preschoolers were evaluated, both genders, aged from four years old to five years and eleven months old who attended a Municipal School of Early Childhood Education in the suburbs of Marilia city- SP. Tympanometry was used as triage procedure. It was considered that the child PASSED in the triage when it presented an A type tympanometric curve, bilaterally, being reevaluated in case of failure. RESULTS: it was observed a high failure index (63.4%) in the studied population. The older female preschoolers presented a higher index of A type tympanograms, in both ears. There was a higher incidence of failure in male preschoolers aged from four years to four years and eleven months. CONCLUSION: in this sample, there was a high index of tympanometric alteration. There was a tendency among younger male students to present a higher index of tympanometric alteration when compared to older female preschoolers, this difference was not statistically significant.